PENERAPAN RAPID APPLICATION DEVELOPMENT PADA APLIKASI AKADEMIK SMP NEGERI 3 MOYO HULU - Jardyagustin, Vinna; Nora Dery Sofya (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
In managing the academic activities of SMP Negeri 3 Moyo Hulu, data and academic needs are still stored in a computer without being accessible to all relevant parties. The imbalance between the number of teachers and students and the lone operator staff has led to limitations in administrative management, such as attendance records and student grade processing. Additionally, the use of loaned applications from other schools for exams has caused inefficient administrative operations and potential data misuse issues. Therefore, the development of a web-based academic application using the Rapid Application Development (RAD) method is necessary to improve efficiency, accuracy, and accessibility in managing academic activities. This application will include features such as student attendance, teacher attendance, class schedules, grade management, exams, and academic information accessible to all relevant parties. It is expected that the implementation of this application will optimize academic activities, facilitate teachers in providing services, and enhance the quality of education.